Pembangunan Desa Industri Berorientasi Tepung Sebagai Satu Sistem Ditinjau dari Aspek Kelembagaan dan Komoditi - Siswadi, Efrain Patola & (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACT The purpose of this research was to known : (1) response of each vertical subsystem if instructed to industrial countryside development orient flour as one system, (2) activities walk from each subsystem horizontal which can be made a arm rest to be developed to become industrial countryside orient flour as one system, (3) role of local government in industrial countryside development orient flour as one system, (4) local commodity which have cultivated in sustaining flour industry which there have and also to be develop, ( 5) possibility of developing commodity introduction in sustaining industrial countryside development orient flour. Data collecting of primary used technique of circumstantial interview (in depth interview) and have the character of opened (open interview), while data collecting of secondary by citing tables or data which available from source data. The results of this research show: (1) all element in vertical subsystem, it was KUD, Private/Industry, BUMN, and the College gave positive response if develop